Foreign Direct Investment In The Banking Sector In New EU Member States: Social Responsibility Of Banks; Bezposŕednie inwestcyje zagraniczne w sektorze bankowym nowych krajoẃ członkowskich Unii Europejskiej: społeczna odpowiedzialnosćb́ankoẃ - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper discusses the performance and strategies of banks with foreign participation in the new EU Member States and their attitudes towards socalled 'socially responsible finance'. The banking sector in the analyzed countries (Czech Republic, Poland and Slovakia) is dominated by foreign capital. The global financial crisis caused a decrease in new annual FDI inflows into the financial intermediation and banking sector of these countries. Some disinvestment occurred in Slovakia and Poland. The foreign-owned banks already operating in the analyzed countries undertook some organizational and financial adjustments to the global economic crisis that allowed them to secure their own position in recipient countries. They are involved in socially responsible activities in the field of culture, sport, environmental protection etc. As trust-based financial institutions. they also showed a kind of responsibility in the field of finance when the crisis occurred. – – Przedmiotem artykułu jest ocena stanu i strategii bankoẃ z udziałem kapitału zagranicznego w nowych krajach członkowskich UE oraz ich podejsćia do kwestii tzw. "społecznie odpowiedzialnych finansoẃ". Sektor bankowy w analizowanych krajach (Czechy, Polska, Słowacja) jest zdominowany przez kapitał zagraniczny. Globalny kryzys finansowy spowodował zmniejszenie sie rocznych strumieni BIZ napływajacych do sektora posŕednictwa finansowego i sektora bankowego tych krajoẃ. W Polsce i Słowacji wystapiły nawet dezinwestycje. Banki z udziałem zagranicznym podjeły organizacyjne i finansowe dostosowania do sytuacji kryzysowej w gospodarce sẃiatowej. Pozwoliło im to zabezpieczycśwoja pozycje w krajach przyjmujacych. Banki te sa zaangazȯwane w społecznie odpowiedzialne działania sferze kultury, sportu, ochrony sŕodowiska itp. Jako instytucje zaufania publicznego wykazały sie roẃniezȯdpowiedzialnosćia w sferze finansoẃ, kiedy ujawnił sie kryzys.
Keywords: 330; Foreign direct investment; banking sector; social responsibility; the New EU Member States